2017
DOI: 10.1145/3092836
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Evaluation of Network-assisted Control Strategies for HTTP Adaptive Streaming

Abstract: This article investigates several network-assisted streaming approaches that rely on active cooperation between video streaming applications and the network. We build a Video Control Plane that enforces Video Quality Fairness among concurrent video flows generated by heterogeneous client devices. For this purpose, a max-min fairness optimization problem is solved at runtime. We compare two approaches to actuate the optimal solution in an Software Defined Networking network: The first one allocates network band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…From this perspective, our main intention with NS-3 simulations in this part of the paper is to illustrate the optimality gap between the BDRA algorithm and other selected rate-fair resource allocation schemes. As a result, with this intention in the paper, we only compare the performance of the BDRA algorithm with other potential resource allocation mechanisms whose operation does not require knowledge about either network throughput rates, or channel quality indicators, or detailed client operation as different from most existing work in the literature [15], [16], [31]- [37].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this perspective, our main intention with NS-3 simulations in this part of the paper is to illustrate the optimality gap between the BDRA algorithm and other selected rate-fair resource allocation schemes. As a result, with this intention in the paper, we only compare the performance of the BDRA algorithm with other potential resource allocation mechanisms whose operation does not require knowledge about either network throughput rates, or channel quality indicators, or detailed client operation as different from most existing work in the literature [15], [16], [31]- [37].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In [53] and [54], the authors have identified three main performance issues: (i) player instability, (ii) unfairness between the players and (iii) the under-utilization of the available bandwidth. It is pointed out that the main cause of these [31], [32], [34], [59] × × × × × [37], [35] ×…”
Section: B Client-side Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent works have studied SAND-DASH in such a context. The authors in [79] design rate-control strategies, such as bandwidth reservation and bitrate guidance, by using edge controllers for SAND-DASH. They also evaluate the proposed streaming schemes in terms of the average video quality received at multiple clients and the fairness in video delivery.…”
Section: E Adaptive Streamingmentioning
confidence: 99%
“…Authors in [11] design a QoEbased SDN architecture that considers the cooperation between network operators and content providers. Further, Cofano et al, [12] investigated several network-assisted streaming strategies that allow active cooperation between the video streaming applications and the network.…”
Section: Related Workmentioning
confidence: 99%